How strategic intent shapes the beliefs and behaviours of senior managers: evidence from a medical technology company. - Nelson, Wayne Brooke (Cranfield University, 2021)
This study employed the critical incident technique to examine how strategic intent shaped the behaviours and beliefs of senior managers in a medical technology company undergoing change. Using this evidence, I contribute a model of the organizational effects of strategic intent, which shows how strategic intent is realized in organizations. In doing so, I also contribute a foundational definition of strategic intent, grounded in the literature employing the concept, but also informed by Action Philosophy. Together, these elements form a common basic theory of strategic intent that brings clarity and coherence to the disparate but related conversations about strategic intent in the literature. Finally, I revisit and add nuance to the resource allocation process and strategic renewal literatures.
Bowman, Cliff - Associate Supervisor
Keywords: Strategic intent; strategic change; strategic renewal; resource allocation process; critical incident technique